2018
DOI: 10.1016/j.cities.2017.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Lahore, Pakistan – Urbanization challenges and opportunities

Abstract: Lahore is the second largest metropolitan in Pakistan, and the capital city of Punjab province. The city hosts various historical monuments, buildings and gardens. Once a walled city during the Mughal era (1524-1752) and British colonial rule, the city has grown as a hub of commerce and trade in the region. The built-up area almost doubled during 1999-2011 and is expected to grow at a similar or even higher rate, hence increasing pressure on the city administration in terms of managing infrastructure and squat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
69
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(92 citation statements)
references
References 14 publications
1
69
0
Order By: Relevance
“…In Pakistan, there is no national or provincial urban planning regulatory authority. This makes things difficult for urban planners to follow neighborhood design regulations, which can vary from city to city, and province to province (Ahmad and Anjum 2012;Rana and Bhatti 2018). Empirical evidences suggest that the environmental component must be acknowledged in neighborhood design, so as to improve livability perception of urbanites.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In Pakistan, there is no national or provincial urban planning regulatory authority. This makes things difficult for urban planners to follow neighborhood design regulations, which can vary from city to city, and province to province (Ahmad and Anjum 2012;Rana and Bhatti 2018). Empirical evidences suggest that the environmental component must be acknowledged in neighborhood design, so as to improve livability perception of urbanites.…”
Section: Resultsmentioning
confidence: 99%
“…The trends of livability in Pakistan vary from urban to urban, urban to rural, and province to province (Parmar and Jalbani 2005). Uncontrolled urban growth has brought forth issues of unequal socioeconomic and infrastructural development (Rana and Bhatti 2018;Rana et al 2017a, b). Small towns of yesteryears have risen as megacities, and this situation has instigated pressures on provision of amenities, and as a result has aggravated current living situations.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the Granger causality test confirmed that there is unidirectional causality running from local food crop production to urbanisation. As Rana and Bhatti (2018) argue, local food crop production is a driver of urbanisation because people are moving from rural areas to urban areas in search of new opportunities and employment. Unlike the studies conducted by Naidu et al (2017) and Naidu (2017), this study could not establish a significant impact of urbanisation on tourism output in the case of Pakistan.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, there is a need to protect and sustain them [1,63]. Lahore, being the second largest urban center of Pakistan (behind Karachi), has more than its fair share of problems, as is often a hallmark of a developing country [64][65][66][67][68]. Urban green spaces in Lahore are under acute pressure, with new demographic trends and the resultant urbanization forcing land-use changes [69,70].…”
Section: Case Studymentioning
confidence: 99%